If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5a+7a=63
We move all terms to the left:
-5a+7a-(63)=0
We add all the numbers together, and all the variables
2a-63=0
We move all terms containing a to the left, all other terms to the right
2a=63
a=63/2
a=31+1/2
| 10-2b=3 | | i=4/3+2/2 | | (r+7)(r-2)=0 | | i=4/3=2/2 | | 5(3x−2)=125 | | 4p+1.6=2.5p+13.3 | | (2n+5)(n-5)=0 | | Y=7.25x+85 | | 9^-10x=17^-x-3 | | (x+4)+(-5x-6)=-32 | | n-40-2=-35 | | 0.3(z–4)=15 | | 7x-21x=-9+3 | | 20=5-5x=5x | | -55=-v/7 | | 4y+115=13y+7 | | n2=98 | | .003x=42000 | | 3.2/x+8=-120 | | 3=2b=5 | | n2=-75 | | (x+4)+(-5x-6)=-36 | | v2=-60 | | 3x=42000 | | 14-3(5h-12)=1-(20h+1) | | n2=9 | | x-16=-7(x+1)-x | | 14x=12x-36 | | x-16=-7(x+1) | | 25=5-15x=3x | | 7g-4=24 | | 4x+16+x=41 |